IMPLEMENTASI SISTEM INFORMASI KEBENCANAAN OTOMATIS SEBAGAI SALAH SATU INOVASI BPBD BALI DALAM MITIGASI BENCANA ALAM - Praditya, Ghifari Yorga; Purnamaningsih, Putu Eka; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2022)
Indonesia is one of the countries that is vulnerable to natural disasters, especially in Bali. The regional disaster management system in Bali has an authorized body, namely BPBD which has the task of formulating and determining disaster management policies by acting quickly, precisely, effectively, and efficiently. Regional natural disaster management system in Bali and regulated in Bali Governor Regulation No. 26 of 2012. This study uses a qualitative descriptive research method, and is analyzed based on the policy implementation model proposed by Charles O. Jones which consists of three indicators, Organization, Interpretation, and Application. The results of this research BPBD Bali Province has an SOP which has two types of services, BPBD Bali has conducted socialization to the community, which is mainly done through social media. However, the problem is that the human resources and financial resources owned by the Bali Province BPBD are still quite small.